Sustainability of Pension Systems in the New EU member States and Croatia : Coping with Aging Challenges and Fiscal Pressures - Kąsek, Leszek; Laursen, Thomas; Skrok, Emilia (Washington, DC : World Bank, 2012)
This report concerns recent pension reforms in Europe. Over the last decade, pension reform has been a major issue on the political agenda across Europe. All European countries are profoundly affected by aging populations resulting from lower fertility and increased life expectancy. In order to make pension systems more sustainable in light of prospective demographic developments, and in some cases to address current financing problems, EU10+1countries have been reforming their pension systems since the mid-1990s. The reforms have combined measures to delay retirement, link benefits more closely to contributions, and diversify risk. Three major forces drive the ageing process: increasing life expectancy, low fertility rates, and finally the baby-boom generation reaching retirement age. All these factors, even in countries where the system is currently fiscally balanced, will produce a major financial challenge for pension systems over the coming decades when the number of pensioners will rapidly increase and the size of the working-age population diminish. This report conclude that some countries (in particular, the Czech Republic, Slovenia, and Romania) will need to do more to safeguard the long-term viability of their pension systems, and others face ongoing and future challenges in ensuring equitable pension systems and adequate living standards for all elderly people.